2021
DOI: 10.1098/rsif.2021.0074
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the early detection of low pathogenic avian influenza H7N9 virus in live bird markets

Abstract: In Southeast Asia, surveillance at live bird markets (LBMs) has been identified as crucial for detecting avian influenza viruses (AIV) and reducing the risk of human infections. However, the design of effective surveillance systems in LBMs remains complex given the rapid turn-over of poultry. We developed a deterministic transmission model to provide guidance for optimizing AIV surveillance efforts. The model was calibrated to fit one of the largest LBMs in northern Vietnam at high risk of low pathogenic H7N9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…Such effective strategies include 5 samples every 2 days, 10 samples every 5 days or 20 samples every 8 days. Which choice of strategy in the event of an outbreak will depend on multiple factors including the aims of the surveillance (early detection or proving absence) ( 22 , 23 ), the cost and availability of sampling and laboratory testing ( 24 , 25 ), the attitudes of farmers ( 26 ) and the wishes of the competent authority, and as such we do not suggest a single ‘best’ strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Such effective strategies include 5 samples every 2 days, 10 samples every 5 days or 20 samples every 8 days. Which choice of strategy in the event of an outbreak will depend on multiple factors including the aims of the surveillance (early detection or proving absence) ( 22 , 23 ), the cost and availability of sampling and laboratory testing ( 24 , 25 ), the attitudes of farmers ( 26 ) and the wishes of the competent authority, and as such we do not suggest a single ‘best’ strategy.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, surveillance that prioritises market operations (e.g., wholesale, retail, both wholesale and retail), animal species, or seasons and time periods presenting higher risks of contamination can be a way to limit costs [ 61 ]. Previous studies have shown it is possible to optimize early detection of avian influenza in live bird markets by minimising trade-offs between surveillance costs and the number of infected birds in live markets at time of detection [ 62 ]. However, more research is needed to assess the capacity of predictive models to anticipate outbreaks based on environmental factors and decision support tools that can consider multiple criteria to identify risks and minimise trade-offs, e.g., the article by M.C.…”
Section: Informing Interventions For Environmentally Driven Zoonoses ...mentioning
confidence: 99%
“…For example, during the COVID-19 pandemic, early detection aided health authorities in identifying infected individuals, thereby slowing the spread of the disease [ 16 , 17 ]. Similarly, for diseases transmitted between animals and humans, early detection and timely implementation of control measures can prevent large-scale transmission within populations [ [18] , [19] , [20] ]. Therefore, it is crucial to establish robust surveillance and response systems that enable early detection and rapid response to emerging zoonotic disease outbreaks before they escalate into epidemics or pandemics [ 5 ].…”
Section: Introductionmentioning
confidence: 99%